Conditions for Convective Deep Inflow - Kuo, Yi‐Hung; Neelin, J. David (Geophysical research letters, 2022)
Observations and cloud‐resolving simulations suggest that a convective updraft structure drawing mass from a deep lower‐tropospheric layer occurs over a wide range of conditions. This occurs for both mesoscale convective systems (MCSs) and less‐organized convection, raising the question: is there a simple, universal characteristic governing the deep inflow? Here, we argue that nonlocal dynamics of the response to buoyancy are key. For precipitating deep‐convective features including horizontal scales comparable to a substantial fraction of the troposphere depth, the response to buoyancy tends to yield deep inflow into the updraft mass flux. Precipitation features in this range of scales are found to dominate contributions to observed convective precipitation for both MCS and less‐organized convection. The importance of such nonlocal dynamics implies thinking beyond parcel models with small‐scale turbulence for representation of convection in climate models. Solutions here lend support to investment in parameterizations at a complexity between conventional and superparameterization. Plain Language Summary Deep convection, whether in isolated thunderstorms or organized mesoscale convective systems, is a leading effect in climate dynamics and climate change, yet it remains subject to large uncertainties in climate models. The way that air enters convective clouds plays a substantial role in this uncertainty, and recently the importance of inflow through a deep layer in the lower troposphere has been noted, although why this should apply for both isolated and organized convection has been unclear. Here, we show that an aspect of dynamics omitted from conventional climate model representations provides a simple explanation for this for large clouds that account for most convective precipitation. This suggests physical effects requiring substantial revisions in climate models. Key Points Observations and simulations point to a common structure of convective mass flux drawing air from a deep layer in the lower troposphere Most deep‐convective precipitation comes from features with horizontal size comparable to or exceeding the lower‐tropospheric depth For these, the nonlocal response of convective updrafts to buoyancy provides a simple explanation for the observed deep‐inflow structure